The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1111/j.1741-3737.2001.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Working Hard and Hardly Working: Domestic Labor and Marital Satisfaction Among Dual‐Earner Couples

Abstract: This article examines the effect of domestic labor, gender ideology, work status, and economic dependency on marital satisfaction using data obtained from self-administered questionnaires for 156 dual-earner couples. Analytic distinctions were drawn among three aspects of domestic labor: household tasks, emotion work, and status enhancement. The effects of each of these elements of the division of domestic labor on marital satisfaction were tested. We also tested the effects of a respondent's satisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
0
12

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 32 publications
(35 reference statements)
12
123
0
12
Order By: Relevance
“…Such feelings of inequity and dissatisfaction are especially likely among working wives who retain responsibility for housework (Frisco and Williams 2003;Stevens, Kiger, and Riley 2001). In her 2004 study, Rogers demonstrated that sharing breadwinning responsibilities lowered married partners' dependency on one another and therefore increased the probability of marital dissolution -a finding consistent with a new home economics argument that role complementarity strengthens marriages (Becker 1981).…”
Section: The Strains Of Egalitarianism? Relationship Stability and Sementioning
confidence: 92%
“…Such feelings of inequity and dissatisfaction are especially likely among working wives who retain responsibility for housework (Frisco and Williams 2003;Stevens, Kiger, and Riley 2001). In her 2004 study, Rogers demonstrated that sharing breadwinning responsibilities lowered married partners' dependency on one another and therefore increased the probability of marital dissolution -a finding consistent with a new home economics argument that role complementarity strengthens marriages (Becker 1981).…”
Section: The Strains Of Egalitarianism? Relationship Stability and Sementioning
confidence: 92%
“…Although working men are more likely to be married, women commit more time to their relationship compared to their partners (Stevens, Kiger, and Riley, 2001). Similarly, women generally spend more time than men on childcare and household chores (Bianchi, Robinson, and Milkie, 2006).…”
Section: Family Determinantsmentioning
confidence: 99%
“…It is possible that there are other explanations for wives' higher stress or lower marital satisfaction, rather than it being the direct result of being in a dualincome couple. For example, the presence or absence of children has a demonstrated effect on marital satisfaction (Meier et al, 2006;Stevens et al, 2001;Twenge, Campbell, & Foster, 2003). As we did not account for this factor in our survey, it could have had an unseen effect on our results.…”
Section: Discussionmentioning
confidence: 89%
“…Women's marital satisfaction is impacted by the perceived equity in labor division, perceived empathy from their husbands, and the opinions that each spouse holds on the wife's employment status and involvement in household activities (Meier et al, 2006;Stevens, Kiger, & Riley, 2001;Wilkie et al, 1998). If women hold traditional beliefs about their responsibilities in the family, their marital satisfaction tends to increase from their greater number of household duties but decrease from the duties they have to their employ ment.…”
Section: Marital Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation